Evaluation of Online Learning Programs (Online) to Improve Santri Digital Literacy at the Khodijah Pemekasan Girls' Islamic Boarding School - Lailatus Sakdiyah; Rusdiana Navlia (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2025)
This research aims to measure how big the results of evaluating online (online) based learning programs are to increase the digital literacy of students at the Khodijah girls' Islamic boarding school. Increasing digital literacy is very important in the current information era, considering the role of Islamic boarding schools in preparing students to face global challenges. The evaluation method applied uses the CIPP (Context, Input, Process, Product) model with a qualitative descriptive approach Data collected through direct observation (case study) and library studies by several books and journals. Research discusses 1). evaluation of online learning programs, 2). The models used in evaluating, one of which is learning used by the CIPP (Context, Input, Process, Product) model, and 3). challenges and opportunities in implementing digital students. 3). Preparing students to fight in the digital world. The research results show that online learning in Islamic boarding schools faces various challenges, such as limited infrastructure and human resource readiness, but also opens up great opportunities in developing digital-based da'wah and learning methods. This evaluation confirms the importance of support for digital literacy programs in Islamic boarding school environments as a strategy to prepare students to face the challenges of the digital era. Researchers hope that the results of this study can contribute as additional insight and reference for the development of Islamic boarding school education in the future.